Determination of prestenotic flow volume using an automated method based on colour Doppler imaging for evaluating orifice area by the continuity equation: validation in a pulsatile flow model. Issue 4 (1st April 1998) - Dennig, K; Nesser, H J; Hall, D; Haase, H U; Schömig, A
Abstract : Objective: To evaluate, in a pulsatile flow model simulating flow conditions in valvar stenoses, whether accurate determination of orifice area can be achieved by the continuity equation using automated determination of flow volumes based on spatiotemporal integration of digital colour Doppler flow velocities. Methods: A method for automated determination of flow volumes which takes into account the velocity distribution across a region of interest was examined using flow through a tube and various restrictive outlet orifices with areas ranging between 0.2 and 3.1 cm 2 . The sampling rectangle of the Doppler method was positioned proximal to the obstructions within the flow convergence zone for evaluating prestenotic flow volume. Stenotic jet velocities were recorded by continuous wave Doppler to obtain the integral under the velocity curve. Prestenotic flow volume was then divided by the velocity integral to calculate functional orifice area according to the continuity equation. Results: The presence of parabolically shaped velocity profiles across the prestenotic region was demonstrated by the Doppler method. Excellent agreement was found between prestenotic flow volumes measured by the Doppler technique and actual values ( r = 0.99, SEE = 1.35 ml, y = 0.99x−0.24). Use of the continuity equation led to a close correlation, with a systematic underestimation of geometric orifice sizes. Correction of Doppler data for flow contraction yielded an excellent agreement with actual orifice areas. Conclusions: The study validated the accuracy of a Doppler method for automated determination of flow volumes for quantifying orifice area by the continuity equation. Prestenotic flow volume and functional orifice area could be evaluated reliably in the presence of non-flat velocity profiles. Thus the method contributes to the non-invasive assessment of valvar stenoses.